About Applied and Theoretical Lexicography of the Buryat Language (towards the issues history) - Babasan Tcyrenov (Oriental Studies, 2018)
The article examines the problem of theoretical interpretation of the Buryat dictionaries. The Buryat language today has several bilingual, one thematic and one brief explanatory dictionaries as well as a number of other special dictionaries. The analysis of work of lexicographers of the past and the present gives an impulse for the further development of the Buryat lexicography.